Pengabaian Kepentingan Alih Teknologi dalam Urgensi Pertumbuhan Investasi Saat Pandemi - Galih Agra Svalerit; Cindy Haura Irawan (Jurnal Hukum Lex Generalis, 2021)
The economic distress caused by the pandemic has prompted the Government to attract investment. The use of foreign workers and the domination of technology become conditions in several foreign investment relations. As the Ministry of Manpower shows more than 29.21 million workers are affected by the pandemic. Investment along with technology transfer should be a solution for developing the Indonesian workforce. However, this contractual agreement does not have a solid legal basis, as a consequence of the imbalance between the parties. The presence of Law Number 11 of 2020 concerning Job Creation is considered not effective for the implementation of the technology transfer.